A study of standard versus tubeless percutaneous nephrolithotomy: Our institutional experience - Rajkumar Ramakrishnan; Senthil Kumar Poovathai; Rajasekar Sundaram; Gopu Rakesh Vamsi; Gulakavarapu Sammohit; Shravankumar Savadatti (Asian Journal of Medical Sciences, 2023)
Background: Percutaneous nephrolithotomy (PCNL) is considered to be the standard procedure in patients with large renal calculus. The purpose of this study is to analyze the evidence-based literature regarding the “nephrostomy-free” or “tubeless” PCNL and to assess the safety, efficacy, possibility, and benefits of tubeless PCNL over standard PCNL. Aims and Objectives: The aim of the study was to review and compare tubeless PCNL with standard PCNL. Materials and Methods: It is a retrospective study done between August 2021 and December 2022. 100 cases of stone disease with stone size more than 2 cm who underwent PCNL in the Department of Urology, Govt hospital, Salem. Patients are divided into two groups (Group A and Group B) of 50 each depending on date of surgery. Results: In our study, we compared tubeless PCNL versus standard PCNL in patients with stone disease. Tubeless PCNL was performed with success in patients of age 13 years–65 years. 36 were female patients, whereas 64 were male patients in this study. All the results were presented in a tabulated form in our study. Conclusion: Tubeless PCNL is a safe and effective technique and is associated with decreased pain, low analgesic requirement, less operating time, and faster recovery. However, it has its own limitation that precludes secondary procedure for the treatment, removal of internal stent, dysuria, and need to visit hospital for subsequent removal of internal stent.